Is old forest like old forest? : patterns in abundance and species number of resident birds in old boreal forest stands in relation to stand structure and landscape context - Leibinger, Ortrud (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2011)
Forest structure and composition may be, dependent on e.g. soil conditions, human impact and forest age, very different, which might result in differences in abundance and species number of resident forest bird. Because of the adverse effects of modern forestry on resident bird species prefer¬ring old growth forest, nature reserves and adapted forest management are needed. However, the plan¬ning of such measures requires an understanding of the factors determining occurrence and abundance of resident forest birds. The aim of this study was to identify habitat variables that are particular important for the abundance and species number of resident birds in old boreal forest patches (≥ 80 years) in the context of two different forest landscapes in northern Sweden. Habitat variables known to be varying with forest age, productivity and degree of human impact were chosen: basal area, basal area of large trees (≥ 40 cm diameter at breast height), coefficient of variation of basal area, basal area of deciduous trees and forest type (pine vs. spruce dominated forest). Generalized linear models were applied to relate the habitat variables, stand area and the factor landscape to abundance and species number data of resident birds, which were obtained by point counts. Besides total abundance and species number abundances of the most abundant single species (Parus major, Poecile montanus, Certhia familiaris and Loxia spp.) and functional bird groups (foliage and trunk glea¬ners, hole nesters and declining species) were analyzed. The total species number and the abundance of the declining species were positively affected by basal area, which was used as indicator for the productivity of the forest and tree canopy closure. The basal of large trees had a positive effect on the total abundance and on the abundance of foliage and trunk gleaners. Because the basal area of large trees was not positively correlated with stand age and site productivity (potential annual timber volume production) it was regarded as indicator for the management intensity of the stands. Total abundance and species number were also positively affected by the area of the investigated stands. Although the total abundance tended to be larger in the less managed landscape, no significant effect of landscape was observed. The effect of basal area on the total species number suggests that productive forests are needed to maintain the whole spectrum of resident bird species. Moreover, productive forests seem to be important for the declining species among the resident birds in the study area. The effect of large trees on total abundance and the abundance of the foliage gleaners might be explained by the greater structural complexity of forests with low management intensity. The results of this study suggest that resident bird species in the study area would benefit from protection and/or restor¬ation of productive and structural complex forests.